An Ethnobotany-Based on Wrapping Plant of Malays Tribe in Meliau Subdistrict - Sabilla, Sabilla Narulita; Sunandar, Ari; Setiadi, Anandita Eka (LPPM Undiksha, 2023)
Utilization of plants as food wrappers is a local wisdom that needs to be preserved. The preservation of traditional knowledge can be done through learning media. This research aims to produce valid learning media and obtain a positive response from students. The research uses Research and Development (R&D) with the ADDIE development model consisting of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection was obtained from interviews, observations, and questionnaires. Data were analyzed using a Likert scale questionnaire. Based on the validation results, the development of an ethnobatany-based encyclopedia on wrapping plants of the Malay Tribe in Meliau Sub-district obtained a highly valid assessment from subject matter experts (91.67%), media experts (95.83%), and valid from language experts (79.86%). In the small-scale trial, 14 students responded positively by 76.67%, and in the large-scale trial, 42 students responded positively by 89.80%, based on aspects of content, language, implementation, and appearance. It can be concluded that the Ethnobotany-based Encyclopedia on wrapping plants of the Malay Tribe in Meliau sub-district, developed as a learning media, is highly suitable for use in the learning process and has received a positive response. The successfully developed encyclopedia media contains the morphological characteristics of plants, food products wrapped with them, and QR codes displaying the process of food wrapping using wrapping plants. This encyclopedia media can also serve as a means of preserving the local wisdom of the Malay community in Meliau Sub-district in utilizing plants as eco-friendly food wrappers.